The xantha Marker Trait Is Associated with Altered Tetrapyrrole Biosynthesis and Deregulated Transcription of PhANGs in Rice - Li, Rui-Qing; Jiang, Meng; Liu, Yan-Hua; Zheng, Yun-Chao; Huang, Jian-Zhong; Wu, Jian-Min; Shu, Qing-Yao (Frontiers in Plant Science, 2017)
The xantha marker trait, which is controlled by a down-regulating epi-mutation of OsGUN4, has been applied to the production of hybrid rice. However, the molecular basis for the ability of xantha mutants to attain high photosynthetic capacity even with decreased chlorophyll contents has not been characterized. In the present study, we observed that the total chlorophyll content of the xantha mutant was only 27.2% of that of the wild-type (WT) plants. However, the xantha mutant still accumulated 59.9% of the WT δ-aminolevulinic acid content, 72.8% of the WT Mg-protoporphyrin IX content, and 63.0% of the WT protochlorophyllide a content. Additionally, the protoporphyrin IX and heme contents in the mutant increased to 155.0% and 160.0%, respectively, of the WT levels. A search for homologs resulted in the identification of 124 rice genes involved in tetrapyrrole biosynthesis and photosynthesis. With the exception of OsGUN4, OsHO-1, and OsHO-2, the expression levels of the genes involved in tetrapyrrole biosynthesis were significantly higher in the xantha mutant than in the WT plants, as were all 72 photosynthesis-associated nuclear genes. In contrast, there were no differences between the xantha mutant and WT plants regarding the expression of all 22 photosynthesis-associated chloroplast genes. Furthermore, the abundance of 1O2 and the expression levels of 1O2-related genes were lower in the xantha mutant than in the WT plants, indicating 1O2-mediated retrograde signaling was repressed in the mutant plants. These results suggested that the abundance of protoporphyrin IX used for chlorophyll synthesis decreased in the mutant, which ultimately decreased the amount of chlorophyll in the xantha mutant. Additionally, the up-regulated expression of photosynthesis-associated nuclear genes enabled the mutant to attain a high photosynthetic capacity. Our findings confirm that OsGUN4 plays an important role in tetrapyrrole biosynthesis and photosynthesis in rice. GUN4, chlorophyll synthesis pathways, and photosynthetic activities are highly conserved in plants and hence, novel traits (e.g., xantha marker trait) may be generated in other cereal crops by modifying the GUN4 gene.